2015
DOI: 10.1021/acs.jchemed.5b00316
|View full text |Cite
|
Sign up to set email alerts
|

Design, Implementation, and Evaluation of a Flipped Format General Chemistry Course

Abstract: Research has consistently shown that active problem-solving in a collaborative environment supports more effective learning than the traditional lecture approach. In this study, a flipped classroom format was implemented and evaluated in the chemistry majors' sequence at Purdue University over a period of three years. What was formerly lecture material was presented online outside of class time using videos of PowerPoint lectures with a voice-over. In-class time was devoted to collaborative problem solving bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
129
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(149 citation statements)
references
References 31 publications
10
129
2
3
Order By: Relevance
“…Relatively weaker students were also found to benefit more than their stronger peers in terms of outcomes on tests in a flipped organic chemistry context (Fautch, 2015). On the other hand, our results offer a counterpoint to most other reports on college learning, which show a general trend of superior performance by students in flipped, inquiry-based, and/or other types of cooperative learning classroom environments (Freeman et al, 2014;Weaver and Sturtevant, 2015;Hibbard et al, 2016;Warfa, 2016). As an illustration, two recent studies specifically in organic chemistry revealed test performance benefits for learners in student-centered, active-learning organic chemistry classrooms (Hein, 2012;Conway, 2014).…”
Section: Classroom Format and Content Knowledgecontrasting
confidence: 79%
“…Relatively weaker students were also found to benefit more than their stronger peers in terms of outcomes on tests in a flipped organic chemistry context (Fautch, 2015). On the other hand, our results offer a counterpoint to most other reports on college learning, which show a general trend of superior performance by students in flipped, inquiry-based, and/or other types of cooperative learning classroom environments (Freeman et al, 2014;Weaver and Sturtevant, 2015;Hibbard et al, 2016;Warfa, 2016). As an illustration, two recent studies specifically in organic chemistry revealed test performance benefits for learners in student-centered, active-learning organic chemistry classrooms (Hein, 2012;Conway, 2014).…”
Section: Classroom Format and Content Knowledgecontrasting
confidence: 79%
“…There is no doubt about the effectiveness of flipped learning in education of general and organic chemistry [8,10,[13][14][15][16]. What is less evident, as there are only a few studies [17,18], is if analytical chemistry is well suited to the flipped teaching Provides a deep understanding of material 9 Encourages more reading outside face-to-face time 3…”
Section: Benefits Of Using Flipped Learning For Delivery Of Analyticamentioning
confidence: 99%
“…Class time then establishes an interactive learning environment where students engage in activities and problem-based learning that are instructor led [5]. Flipped learning has been widely applied in STEM subjects, notably in the delivery of physics, engineering, and mathematics [3,4,8], and its use in chemistry teaching is increasing, with various studies being published on the delivery of organic or general chemistry in this way [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…These results corroborate some of the more recent findings regarding the use of flipped pedagogical techniques in college-level general chemistry courses. 37,44,45 While some of the activities and assessment methods described (e.g., gated testing) may only be conveniently utilized in smaller classroom settings, many of these strategies described in this paper can be applied in large classrooms and in a variety of chemistry courses.…”
Section: ■ Conclusion and Future Workmentioning
confidence: 99%